Downgrade BI-RADS 4A Patients Using Nomogram Based on Breast Magnetic Resonance Imaging, Ultrasound, and Mammography - Xie, Yamie; Zhu, Ying; Chai, Weimin; Zong, Shaoyun; Xu, Shangyan; Zhan, Weiwei; Zhang, Xiaoxiao (Frontiers in Oncology, 2022)
Objectives To downgrade BI-RADS 4A patients by constructing a nomogram using R software. Materials and Methods A total of 1,717 patients were retrospectively analyzed who underwent preoperative ultrasound, mammography, and magnetic resonance examinations in our hospital from August 2019 to September 2020, and a total of 458 patients of category BI-RADS 4A (mean age, 47 years; range 18–84 years; all women) were included. Multivariable logistic regression was used to screen out the independent influencing parameters that affect the benign and malignant tumors, and the nomogram was constructed by R language to downgrade BI-RADS 4A patients to eligible category. Results Of 458 BI-RADS 4A patients, 273 (59.6%) were degraded to category 3. The malignancy rate of these 273 lesions is 1.5% (4/273) (<2%), and the sensitivity reduced to 99.6%, the specificity increased from 4.41% to 45.3%, and the accuracy increased from 63.4% to 78.8%. Conclusion By constructing a nomogram, some patients can be downgraded to avoid unnecessary biopsy.